Training of librarians and information professionals in the Faculty of Information Management, UiTM: past, present and future / Raja Abdullah Yaacob ... [et al.] - Yaacob, Raja Abdullah; Jamaludin, Adnan; Hashim, Laili; Mohd Nadzar, Fuziah; Abdul Manaf, Zuraidah; Mat Isa, Azman (Fakulti of Information Management, Universiti Teknologi MARA, 2012)
The library and information profession has emerged as the axial profession. providing the knowledge and skills on which society may advance and compete using new critical resource. The Faculty of Information Management (FIM), Universiti Teknologi MARA (UiTM), has played a pivotal role in providing relevant competencies for the continuously emerging need of a new breed of information professionals (IPs). FIM has been the pioneer in the education and training of library and IPs in Malaysia, and his propels it to provide maximum avenue and capacity to facilitate it to remain as the leader in the training responsibility in the country. The increase in the number of programs and student population is in response to its vision and objective to achieve excellence in fulfilling the increasing demand for new breeds of library and IPs. This is in line with the advancement of knowledge in the digital era and the need for new competencies. Sinceits establishment in 1968, the faculty has evolved in its programs in line with societal, environmental and technological changes. The development of professional library and information curriculum takes into consideration both the theoretical and practical knowledge, analytical innovations and averts information overload. The curriculum is developed, with the view for the retaining and reskilling of librarians and IPs. At this critical juncture, new competencies are needed for the new breed of IPs, calling for active process of learning, relearning, and unlearning. The ongoing development of advanced technologies in libraries and information agencies has placed a high priority on ICT and knowledge competencies among library staff and IPs, and the faculty will continue to move according to the needs of the market.